Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know I am messing up something with the substitutions but I am not sure what.

$$\int \sqrt{1-4x^2}$$

$$u = 4x, du = 4 \,dx$$

$$\frac{1}{4}\int \sqrt{1-u^2}$$

$u = \sin \theta$

$$\frac{1}{4}\int \sqrt{1-\sin^2 \theta} = \frac{1}{4}\int \sqrt{ \cos^2 \theta} = \frac{1}{4}\int \cos \theta = \frac{\sin \theta}{4}$$

Replace $\theta$ with $u$

$$\frac{\sin (\arcsin u)}{4} = \frac{u}{4} = \frac{4x}{4} = x$$

This is wrong and I have no idea why.

share|cite|improve this question
It is $u=2x$. So we get $du=2\,dx$ and end up with $\int 2\sqrt{1-u^2}\,du$. Then $u=\sin\theta$. Remember (you have been doing so lately, but slipped) that $du=\cos\theta\,d\theta$. Please don't forget to write integrals properly. The substitution went wrong probably because you wrote $\int\sqrt{1-u^2}$ instead of $\int\sqrt{1-u^2}\,du$. I know, that $d$ stuff is a nuisance, but it helps protect against error. – André Nicolas Jun 4 '12 at 17:26
By your substitution $u=4x$, you have $$\begin{equation*} \int \sqrt{1-4x^{2}}dx=\int \sqrt{1-4\frac{1}{4^{2}}u^{2}}\,\frac{1}{4} du=\int \frac{1}{4}\sqrt{1-\frac{1}{4}u^{2}}\,du \end{equation*}$$ – Américo Tavares Jun 4 '12 at 17:26
Don't forget the $+C$! – TMM Jun 4 '12 at 17:35
I do not follow this at all. – user138246 Jun 4 '12 at 17:37
I do not understand how to manipulate equations through 2 sets of variables. – user138246 Jun 4 '12 at 18:00
up vote 8 down vote accepted

$$\int \sqrt{1-4x^2}\ dx$$ Substitute $$\begin{align*}x &= \frac{\sin (\theta)}{2}\\ dx &= \frac{\cos(\theta)}{2}d \theta\end{align*}$$ So the intregral become $$\begin{align*} \int \sqrt{1-4x^2}\ dx &=\frac{1}{2}\int \cos^2(\theta)d\theta\\ &=\frac{1}{2}\int \frac{\cos(2\theta) + 1}{2}d\theta\\ &=\frac{\sin(2\theta)}{8}+\frac{\theta}{4} \end{align*}$$ Again $$\theta = \arcsin(2x)$$ And $$\begin{align*} \sin 2\theta &= 2\sin \theta \cos \theta\\ &=4x\sqrt{1-4x^2} \end{align*}$$ So the answer is $$\frac{x\sqrt{1-4x^2}}{2}+\frac{\arcsin(2x)}{4}+C$$

share|cite|improve this answer
I do not see how this works, it looks like have sin/2 will not work. How does that work? Also I do not follow the part after "So the integral become" it looks like you forgot to take the square root. – user138246 Jun 4 '12 at 18:15
@Jordan see i have used sin(x)/2 so that inside squareroot 4 will vanish and we will be left with cos(x) and another cos(x)/2 will come when we $dx = \cos(\theta)/2 d \theta$ hence the $cos^2(\theta)/2$ – Saurabh Jun 4 '12 at 18:21
@Jordan with that change of variables: $$\sqrt{1-4x}dx=\sqrt{1-4\left(\frac{\sin\theta}{2}\right)^2}\frac{\cos\theta}{2‌​}\ d\theta,$$ can follow from here? – leo Jun 4 '12 at 18:22
@SaurabhHota nice answer. Please don't forget to add a constant to the result. – leo Jun 4 '12 at 18:23
@Jordan It is as is because: $$\begin{align*} \sqrt{1-4x}dx&=\sqrt{1-4\left(\frac{\sin\theta}{2}\right)^2}\frac{\cos\theta}{2‌‌​​}\ d\theta\\ &= \sqrt{1-4\cdot\frac{\sin^2\theta}{4}}\frac{\cos\theta}{2}\ d\theta\\ &=\sqrt{1-\sin^2\theta}\frac{\cos\theta}{2}\ d\theta \end{align*}$$ and you know what $\sqrt{1-\sin^2\theta}$ is, right? – leo Jun 4 '12 at 18:31

You should substitute $u=2x$, to get the next integral:

$$\int du/2 \sqrt{1-u^2}$$

Now change variables to $u=\cos(t)$ to get:

$$-\int (\sin(t)/2) \sin(t) dt$$ which you solve by parts or by using the formula for $\cos(2\theta)$.

Hope I helped.

share|cite|improve this answer
I do not quit follow what happened here. Why would I use 2x instead of 4x? That seems counter intuitive. – user138246 Jun 4 '12 at 17:21
You want the $4x^2$ to be replaced by $u^2$, so you want $4x^2=u^2$. To solve for $u$, take square roots of both sides to get $u=2x$. – John Engbers Jun 4 '12 at 17:26
I have no idea what is happening, where did the du go? – user138246 Jun 4 '12 at 17:38
@Jordan better question: where did the du go in your attempt? The du here was transformed into $-\sin(t)dt$. – Robert Mastragostino Jun 4 '12 at 18:11

Some things to watch out for:

  1. As already mentioned, if you substitute $u = 4x$, then you get $u^2 = (4x)^2 = 16x^2$ instead of $u^2 = 4x^2$. If you use $u = 2x$, then $u^2 = (2x)^2 = 4x^2$.
  2. An annoying but important part of practicing good mathematics is being precise.

    • In your integrals, you forgot the $dx$ and $du$ several times, which also lead you to forget to express $du$ in terms of $d\theta$. Perhaps you have heard of Riemann integrals; these may help you understand why the "$dx$" is there.
    • You forgot the fact that if $F'(x) = f(x)$, then $\int f(x) dx = F(x) + C$. After all, when taking derivatives, all constants disappear, so the derivatives of $F(x)$ and $F(x) + 5$ are exactly the same. Thus, when calculating indefinite integrals, you do not know the constant term of the resulting function. So we generally write $\int f(x) dx = F(x) + C$ for some unknown constant $C$.

Here's a step-by-step approach of how I would do it. First, substitute $u = 2x$, so that $u^2 = (2x)^2 = 4x^2$, and apply $du = 2dx$:

$$\int \sqrt{1 - \color{red}{4x^2}} \color{blue}{dx} = \int \sqrt{1 - \color{red}{u^2}} \color{blue}{\frac{du}{2}} = \frac{1}{2} \int \sqrt{1 - u^2} du.$$

Then substitute $u = \sin \theta$ and $du = \cos \theta d\theta$ to get:

$$\frac{1}{2} \int \sqrt{1 - \color{red}{u^2}} \color{blue}{du} = \frac{1}{2} \int \sqrt{1 - \color{red}{\sin^2 \theta}} \color{blue}{\cos \theta d\theta} = \frac{1}{2} \int \sqrt{\cos^2 \theta} \cos \theta d\theta = \frac{1}{2} \int \cos^2 \theta d\theta.$$

Next, apply the double angle formula for the cosine, $\cos^2 \theta = \frac{1}{2} (1 + \cos 2\theta)$, to get

$$\frac{1}{2} \int \color{red}{\cos^2 \theta} d\theta = \frac{1}{2} \int \color{red}{\frac{1 + \cos 2\theta}{2}} d\theta = \frac{1}{4} \int (1 + \cos 2\theta) d\theta.$$

Now split in two integrals and calculate those separately:

$$\frac{1}{4} \int (\color{red}{1} + \color{blue}{\cos 2\theta}) d\theta = \frac{1}{4} \left(\int \color{red}{1} d\theta + \int \color{blue}{\cos 2\theta} d\theta\right) = \frac{1}{4}\left(\color{red}{\theta + C_1} + \color{blue}{\frac{\sin 2\theta}{2} + C_2}\right) \\ = \frac{\theta}{4} + \frac{\sin 2\theta}{8} + C.$$

Applying a double angle formula for the sine, $\sin 2\theta = 2 \sin \theta \cos \theta$, we get

$$\frac{\theta}{4} + \frac{\color{red}{\sin 2\theta}}{8} + C = \frac{\theta}{4} + \frac{\color{red}{2 \sin \theta \cos \theta}}{8} + C = \frac{\theta}{4} + \frac{\sin \theta \cos \theta}{4} + C.$$

Substituting back $\theta = \arcsin u$, and using $\cos (\arcsin u) = \sqrt{1 - u^2}$, we get

$$\frac{\color{red}{\theta}}{4} + \frac{\sin \color{blue}{\theta} \cos \color{green}{\theta}}{4} + C = \frac{\color{red}{\arcsin u}}{4} + \frac{\sin(\color{blue}{\arcsin u}) \cos(\color{green}{\arcsin u})}{4} + C = \frac{\arcsin u}{4} + \frac{u \sqrt{1 - u^2}}{4} + C.$$

Finally substituting $u = 2x$, you get

$$\frac{\arcsin \color{red}{u}}{4} + \frac{\color{blue}{u} \sqrt{1 - \color{green}{u}^2}}{4} + C = \frac{\arcsin \color{red}{2x}}{4} + \frac{\color{blue}{2x} \sqrt{1 - \color{green}{(2x)}^2}}{4} + C = \boxed{\displaystyle\frac{\arcsin 2x}{4} + \frac{x \sqrt{1 - 4x^2}}{2} + C}.$$

share|cite|improve this answer
Why is cosarcsin u equal to that statement? – user138246 Jun 4 '12 at 19:26
@Jordan See for instance the paragraph "But... what is $\cos(\arcsin(u))$?" in this answer to another question. – TMM Jun 4 '12 at 19:37

Let $2x = u$. So, $dx = \frac{1}{2}du$ $$\frac{1}{2}\int \sqrt{1-u^2} du$$ Replace $u = \sin \theta$, $du = cos \theta\ d\theta$

So, equation will be
$$\frac{1}{2}\int \sqrt{1-sin^2 \theta}\ cos\theta\ d\theta$$ $$\frac{1}{2}\int \sqrt{\cos^2\theta}\ cos\theta\ d\theta$$ $$\frac{1}{2}\int cos^2\theta\ d\theta$$ Add and subtract $\frac{1}{4}\int d\theta$ $$\frac{1}{4}\int 2cos^2\theta\ d\theta - \frac{1}{4}\int d\theta + \frac{1}{4}\int d\theta$$ $$\frac{1}{4}\int (2cos^2\theta-1)\ d\theta+ \frac{1}{4}\int d\theta$$ $$\frac{1}{4}\int (2cos^2\theta-1)\ d\theta+ \frac{1}{4}\int d\theta$$ $$\frac{1}{4}\int \cos2\theta\ d\theta+ \frac{1}{4}\int d\theta$$ $$\frac{1}{8} (\sin2\theta) + \frac{1}{4} \theta + C$$ $$\frac{1}{8} (2\sin\theta.\cos\theta) + \frac{1}{4} \theta + C$$ As u = $\sin\theta$ $$\frac{1}{4} (u\sqrt{1-u^2}) + \frac{1}{4} \sin^{-1}u + C$$ As $2x = u$ $$\frac{1}{4} (2x\sqrt{1-4x^2}) + \frac{1}{4} \sin^{-1}2x + C$$ $$\frac{1}{2} (x\sqrt{1-4x^2}) + \frac{1}{4} \sin^{-1}2x + C$$

share|cite|improve this answer
What happened to the 4? – user138246 Jun 4 '12 at 17:56
@Jordan : Just wait for a second, I am not completed yet – rekenerd Jun 4 '12 at 18:00
@Jordan : 4 in which step? – rekenerd Jun 4 '12 at 18:04

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.